I leaerned this neat trick
you don't need to convert to vertex form
where
y=ax^2+bx+c
the x value of the vertex is -b/2a
the y value is found by inserting the x value of the vertex into the equation
so
1x^2-6x+14
-b/2a=-(-6)/2(1)=6/2=3
plug that in
y=x^2-6x+14
y=3^2-6(3)+14
y=9-18+14
y=5
the vertex is (3,5)
Answer is 5060 m
hope it helps
Answer:
wouldn't be $240 why u keep deleting my answer
Answer:
<h2>

</h2>
Step-by-step explanation:
<em><u>Given</u></em><em><u>, </u></em>

<em><u>Since</u></em><em><u>,</u></em>

<em><u>Hence</u></em><em><u>,</u></em>

<em><u>Since</u></em><em><u>,</u></em>

<em><u>Hence</u></em><em><u>,</u></em>
